2003
DOI: 10.1007/s00027-003-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multi-year experimental flood regime on macroinvertebrates downstream of a reservoir

Abstract: Abstract.We examined the response of stream macroinvertebrates to a multiple-year experimental flood regime downstream of a large reservoir. Benthic samples were collected from the River Spöl prior to the initial flood (1999) and at periodic intervals before and after eight floods from 2000 through 2002. Three artificial floods occurred each in 2000 and 2001, and two floods were implemented in 2002. We also sampled macroinvertebrates in an adjacent tributary (Val da l'Aqua) on the same dates as in the Spöl to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 48 publications
7
86
1
2
Order By: Relevance
“…Baetidae mayflies and Chironomidae midges recovered very quickly post-flood, a result generally attributed to the mobility of their adult stages (Robinson et al 2003). Blackflies also typically return quickly (Robinson et al 2003), although their recovery was very protracted in both Trout Run and the Middle Branch in the present study. The larger Ephemerellidae mayflies and Hydropsychidae caddisflies were greatly reduced in the Middle Branch and virtually absent from Trout Run for a year after flooding.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Baetidae mayflies and Chironomidae midges recovered very quickly post-flood, a result generally attributed to the mobility of their adult stages (Robinson et al 2003). Blackflies also typically return quickly (Robinson et al 2003), although their recovery was very protracted in both Trout Run and the Middle Branch in the present study. The larger Ephemerellidae mayflies and Hydropsychidae caddisflies were greatly reduced in the Middle Branch and virtually absent from Trout Run for a year after flooding.…”
Section: Discussionsupporting
confidence: 44%
“…It required over a year for amphipod densities in Trout Run to reach normal levels, but Middle Branch numbers remained at minimal levels nearly 2 years post-flood. Reduced taxa richness and changes in community structure are typical of benthic invertebrate assemblages subjected to severe flooding (e.g., Hynes 1970;Lytle 2000;Robinson et al 2003;Snyder and Johnson 2006;Elzinga et al 2009). In the streams of Whitewater State Park, taxa were lost and community structure modified, but only in the smaller systems.…”
Section: Discussionmentioning
confidence: 99%
“…Flow regime has a strong influence on the biodiversity of rivers and importance of keeping the flow as close as possible to the natural regime is attested (Stanford et al, 1996;Poff et al, 1997) and confirmed by the interest in restoring natural flow regime to recover biotic integrity all around the world (Sparks, 1995;Petts, 1996;Galat et al, 1998;Sparks et al, 1998;Dudgeon, 2000;Robinson et al, 2003;Attwood & Cottet, same issue).…”
Section: Discussion -Conclusionmentioning
confidence: 94%
“…Slides for diatoms are examined using a Nikon microscope (Eclipse 600) and, when necessary, by scanning electron microscopy (SEM; JEOL JSM 35 CF). A minimum of 250 diatom valves are counted and identified along random transects from each slide based on the keys of Krammer & LangeBertalot (1991, 1999a, b, 2000, Round et al (1990), Lange-Bertalot & Moser (1994), and Lange-Bertalot & Metzeltin (1996).…”
Section: Long-term Biomonitoring Protocolmentioning
confidence: 99%